2014
DOI: 10.1111/hsc.12133
|View full text |Cite
|
Sign up to set email alerts
|

Use of quality information in decision-making about health and social care services - a systematic review

Abstract: What is known about this topic• Quality reporting for health and social care providers was introduced in response to concerns over the quality of services in various countries over the past decades.• Studies in the general population and user surveys found limited awareness and low use of available quality information in health and long-term care. What this paper adds• There is a mismatch between the provided quality information and the information needs of service users.• Trust is a key issue in relation to q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 45 publications
1
40
0
4
Order By: Relevance
“…Caregivers do not tend to self-identify or ask for support. There is an expectation that family physicians will refer patients and families to the appropriate services and supports and information from physicians is highly valued, but may not be offered in a timely manner (Turnpenny & Beadle-Brown, 2015). Family caregivers now spend 15%-50% of their time negotiating health and social care systems, and then managing the care and services from siloed health and social care services (Taylor & Quesnel-Vallée, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers do not tend to self-identify or ask for support. There is an expectation that family physicians will refer patients and families to the appropriate services and supports and information from physicians is highly valued, but may not be offered in a timely manner (Turnpenny & Beadle-Brown, 2015). Family caregivers now spend 15%-50% of their time negotiating health and social care systems, and then managing the care and services from siloed health and social care services (Taylor & Quesnel-Vallée, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There are significant continuities in barriers and facilitators to information‐sharing identified within this exploratory study and other empirical studies. For example, in relation to carers' reliance on informal sources for advice and information about respite services (Turnpenny & Beadle‐Brown ); carers' frustrations when services did not meet their expectations (Shaw et al . , Greenwood et al .…”
Section: Discussionmentioning
confidence: 99%
“…There are significant continuities in barriers and facilitators to information-sharing identified within this exploratory study and other empirical studies. For example, in relation to carers' reliance on informal sources for advice and information about respite services (Turnpenny & Beadle-Brown 2014); carers' frustrations when services did not meet their expectations (Shaw et al 2009, Greenwood et al 2012; apprehension about handing over care (Forbes et al 2012, Phillipson et al 2014; and the risks associated with information-sharing being hurried or based on standardised communications (Payne et al 2002, McPherson et al 2014, Wilson et al 2015. The multiple accounts elicited from carers taking part in our study, however, identified how barriers and facilitators to information-sharing with respite services changed over time.…”
Section: Discussionmentioning
confidence: 99%
“…Nor does it fully consider different motives for seeking I&A, different individual practices and interactions with different forms of information and or advice or other yet to be determined nuances -or even whether the formal imparted I&A was used at all (Turnpenny and Beadle-Brown, 2014).…”
Section: Need For Deeper Enquir Y and Qualitative Methods Around Agencymentioning
confidence: 99%
“…However, it is also evident that accessing information does not always have its intended effect in informing and enabling consumers in a welfare context. Furthermore, because formal information is often inaccessible, informal and subjective, the sources of support often prove to be more important in shaping welfare decision-making (Turnpenny and Beadle-Brown, 2014). However, these sources may not always be of high quality or be based on robust evidence.…”
Section: Introduction and Policy Contextmentioning
confidence: 99%